(3x-1)(2-x)-x(x+3)=2

Simple and best practice solution for (3x-1)(2-x)-x(x+3)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-1)(2-x)-x(x+3)=2 equation:


Simplifying
(3x + -1)(2 + -1x) + -1x(x + 3) = 2

Reorder the terms:
(-1 + 3x)(2 + -1x) + -1x(x + 3) = 2

Multiply (-1 + 3x) * (2 + -1x)
(-1(2 + -1x) + 3x * (2 + -1x)) + -1x(x + 3) = 2
((2 * -1 + -1x * -1) + 3x * (2 + -1x)) + -1x(x + 3) = 2
((-2 + 1x) + 3x * (2 + -1x)) + -1x(x + 3) = 2
(-2 + 1x + (2 * 3x + -1x * 3x)) + -1x(x + 3) = 2
(-2 + 1x + (6x + -3x2)) + -1x(x + 3) = 2

Combine like terms: 1x + 6x = 7x
(-2 + 7x + -3x2) + -1x(x + 3) = 2

Reorder the terms:
-2 + 7x + -3x2 + -1x(3 + x) = 2
-2 + 7x + -3x2 + (3 * -1x + x * -1x) = 2
-2 + 7x + -3x2 + (-3x + -1x2) = 2

Reorder the terms:
-2 + 7x + -3x + -3x2 + -1x2 = 2

Combine like terms: 7x + -3x = 4x
-2 + 4x + -3x2 + -1x2 = 2

Combine like terms: -3x2 + -1x2 = -4x2
-2 + 4x + -4x2 = 2

Solving
-2 + 4x + -4x2 = 2

Solving for variable 'x'.

Reorder the terms:
-2 + -2 + 4x + -4x2 = 2 + -2

Combine like terms: -2 + -2 = -4
-4 + 4x + -4x2 = 2 + -2

Combine like terms: 2 + -2 = 0
-4 + 4x + -4x2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(-1 + x + -1x2) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-1 + x + -1x2)' equal to zero and attempt to solve: Simplifying -1 + x + -1x2 = 0 Solving -1 + x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. 1 + -1x + x2 = 0 Move the constant term to the right: Add '-1' to each side of the equation. 1 + -1x + -1 + x2 = 0 + -1 Reorder the terms: 1 + -1 + -1x + x2 = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x + x2 = 0 + -1 -1x + x2 = 0 + -1 Combine like terms: 0 + -1 = -1 -1x + x2 = -1 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. -1x + 0.25 + x2 = -1 + 0.25 Reorder the terms: 0.25 + -1x + x2 = -1 + 0.25 Combine like terms: -1 + 0.25 = -0.75 0.25 + -1x + x2 = -0.75 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = -0.75 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 9-7x=20+4x | | 5hm=h+28k | | 4z+10-2z=6+z+8 | | x(2x+7)-5=(x+4)(5-x) | | 6x^2+27x-15=0 | | x+y=85 | | 5/9(F-32)= | | (4.6)(-2.25)= | | A=7+3x(5+49*7) | | 6n+8=3n+36 | | (-1.2)(-3.1)= | | x+x+20+4x-33=677 | | 4a+5+6a= | | (5x-8)(4-3x)+x(4-x)=0 | | -21(3)= | | 6+2p-4=6p+16-2p | | 4(-8)= | | 4+2x=x-9 | | 4.8-10= | | a+(17+a)+(4a-35)=900 | | -9(z-1)=5-8z | | 1.5-9.6= | | 2+3a= | | 5z+3z=7z+3 | | -5X^2+5X-4=-X^2-7X+5 | | p=76l+128w | | -5(4x-2)+12x=-6 | | x+x+350000=550000000 | | -21-4= | | 5x^2-13x+2=0 | | 8-(-4)= | | -14-(-2)= |

Equations solver categories